THE INFLUENCE OF PRICE, PRODUCT QUALITY, AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF DOA IBU COFFEE SHOP IN DEPOK CITY - Muhammad Fikri Nurdiansyah; Suadi Sapta Putra; Kumba Digdowiseiso (SEAN Institute, 2023)
This research aims to determine the influence of price, product quality and service quality on customer satisfaction at the Doa Ibu coffee shop in Depok City. The population in this study used a random sampling technique, where the population taken was 100 people with a significance level of 95% and a standard deviation of 25%. This research uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results of the research show that price has a positive effect on customer satisfaction at Doa Ibu coffee shop in Depok City. Product quality has a positive effect on customer satisfaction at Doa Ibu coffee shop in Depok City. And service quality has a positive effect on customer satisfaction at Doa Ibu coffee shop in Depok City.